TEACHING WRITING THROUGH CRITICAL THINKING (International Conference on Economics, Finance, Banking and Management, 2025)
This article explores the integration of critical thinking into writing instruction as a method for enhancing students’ cognitive engagement, argumentation skills, and overall writing proficiency. Grounded in constructivist pedagogy and cognitive learning theories, the article outlines practical strategies for educators to foster analytical writing. It highlights how encouraging students to question assumptions, analyze evidence, and synthesize diverse viewpoints strengthens both their critical faculties and written expression. The paper concludes with classroom implications, challenges, and recommendations for future research.